Diagnostic Value of miR-103 in Patients with Sepsis and Noninfectious SIRS and Its Regulatory Role in LPS-Induced Inflammatory Response by Targeting TLR4. (13th May 2020) - Yang, Min; Zhao, Li; Sun, Mingyan
Abstract : Background . Sepsis is a life-threatening condition and a systemic inflammatory response syndrome (SIRS) driven by infection. This study aimed at investigating the expression of microRNA-103 (miR-103) in sepsis patients, evaluating its diagnostic value, and exploring the regulatory effect of miR-103 on LPS-induced inflammation in monocytes. Methods . Expression of miR-103 was measured using quantitative real-time PCR. A receiver operating characteristics curve was plotted to evaluate the diagnostic vale of miR-103. Serum and cell supernatant levels of proinflammatory cytokines were analyzed using ELISA. The interaction between miR-103 and Toll-like receptors 4 (TLR4) was analyzed using luciferase reporter assay. The effect of miR-103 on inflammation was examined in LPS-treated monocytes. Results . Serum expression of miR-103 was decreased in noninfectious SIRS and sepsis patients compared with healthy controls, and the lowest expression value was observed in sepsis patients (all P < 0.05 ). Serum levels of miR-103 have considerable diagnostic accuracy in distinguishing sepsis patients from SIRS patients and healthy controls. A negative correlation was found between miR-103 and inflammatory responses in sepsis patients. TLR4 was demonstrated to be a direct target of miR-103 and was negatively regulated by miR-103 in monocytes. The promoted inflammatory responses by LPS in monocytes were reversed by the overexpression of miR-103. Conclusion . All the data revealed that serum decreased miR-103 in sepsis patients serves as a promising noninvasive diagnostic biomarker and may be involved in the pathogenesis of sepsis by regulating inflammatory responses via targeting TLR4.